Critical current characteristics of YBa2Cu3O 7 thin films on (110) SrTiO3. - Cukauskas, E.J.
The material and electrical characteristics of YBa2Cu 3O7 (YBCO) thin films deposited by inverted cylindrical magnetron sputtering on (110) SrTiO3 (STO) were investigated. X-ray diffractometry shows the grain orientations to be predominantly the YBCO (110) and (103) with no evidence of c-axis grains, Electron micrographs show the film surface to consist of coupled elongated grains parallel to the (110) STO edge. The films were patterned into small 2.5 mm squares parallel to the substrate edges for electrical characterization. Transport currents parallel and perpendicular to the (110) substrate edge showed a 945:1 anisotropy in film resistance and a factor of two in critical current density for temperatures below 60% of the transition temperature (Tc). The temperature dependence of the critical current near Tc was quadratic-like and strongly dependent on the value of Tc used in the analysis. For the two orientations, there was nearly a 6 K difference in Tc as determined by the point at which the critical current became zero. The response of the critical current to small magnetic fields was greater for transport current along the c-axis direction and was observable over a temperature interval nearly four times greater than for current along the basal plain. These YBCO thin films have good response to small magnetic fields and are suitable for vortex flow device development
Keywords: 2.5 mm; SrTiO3.; SrTiO3(110) substrate; X-ray diffractometry; YBa2Cu3O7.; Coupled elongated grains; Critical current; Critical current density; Grain orientation; Inverted cylindrical magnetron sputtering; Temperature dependence; Thin films; Transition temperature; Vortex flow device